Ocean energy : technology readiness, patents, deployment status and outlook (International Renewable Energy Agency, 2014)
The potential of oceans as an energy source is staggering - more than sufficient to meet global electricity demand well into the future. Ocean resources vary from tidal currents and waves, to temperature and salinity gradients. Ocean energy technologies could contribute to energy independence, decarbonisation and job creation. Existing patents and announced projects span the globe, with hotspots of activity in the UK, France, USA, Australia, Canada, France, Japan, the Republic of Korea, the United Kingdom and the United States. Yet the contribution of ocean energy to the world's energy mix remains very small, with key technologies still in development and demonstration phases. For most ocean energy technologies, the main challenge is to reduce costs and improve system reliability and performance, in order to ensure sustained, commercially competitive energy costs.